Information society and the workplace : spaces, boundaries and agency - Heiskanen, Tuula; Hearn, Jeff, 1947- (Routledge, 2004)
Bringing together studies of everyday local practices in workplaces within information society, this book has a special focus on social space and the agency of actors. it includes both theoretical reviews and qualitative research.
Keywords: Information society.; Industrial sociology.; Société de l'information.; Sociologie industrielle.; COMPUTERS -- Information Technology.; Industrial sociology; Information society; Informationssamhället.; Kunskapsöverföring.